A Rhodnius prolixus Insulin Receptor and Its Conserved Intracellular Signaling Pathway and Regulation of Metabolism - Defferrari, Marina S.; Da Silva, Sara R.; Orchard, Ian; Lange, Angela B. (Frontiers in Endocrinology, 2018)
The insulin signaling pathway is a modulator of metabolism in insects and can regulate functions associated with growth and development, as well as lipid and carbohydrate balance. We have previously reported the presence of an insulin-like peptide and an insulin-like growth factor in Rhodnius prolixus, which are involved in the homeostasis of lipids and carbohydrates in post-feeding and non-feeding periods. In the present study, we have characterized the first insulin receptor (IR) to be discovered in R. prolixus, Rhopr-IR, and investigated its intracellular signaling cascade and its role in nutrient control. We identified a candidate protein sequence within R. prolixus putative peptidome and predicted its conserved features using bioinformatics. Tissue-specific expression analyses indicated that the Rhopr-IR transcript is differentially-expressed in all tissues tested, with the highest values observed in the central nervous system (CNS). Treatment of insects with the IR kinase activator BpV(phen), glucose, or porcine insulin resulted in the activation of protein phosphorylation in the fat body, and stimulated the phosphorylation of protein kinase Akt, an evolutionarily conserved key regulator of the intracellular insulin signaling cascade. We also observed activation of Akt and phosphorylation of its downstream targets glycogen synthase kinase 3 β (GSK3β) and the transcription factor FOXO for several days following a blood meal. We used dsRNA to knockdown transcript expression and examined the resulting effects on metabolism and intracellular signaling. Furthermore, knockdown of the Rhopr-IR transcript increased lipid levels in the hemolymph, while reducing lipid content in the fat body. Interestingly, the levels of carbohydrates in the hemolymph and in the fat body did not show any alterations. The activation of Akt and phosphorylation of FOXO were also reduced in knockdown insects, while the phosphorylation pattern of GSK3β did not change. Our results support the identification of the first IR in R. prolixus and suggest that Rhopr-IR signaling is involved in hemolymph nutrient homeostasis and fat body storage both in post-feeding and in nonfeeding stages. These metabolic effects are likely regulated by the activation of Akt and downstream cascades similar to mammalian insulin signaling pathways.